The Effect Of Fathering On Dating Intimacy In Early Adult Women - Buulolo, Gres Ananta; Aritonang, Nancy Naomi (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This study aims to determine the influence of fathering on dating intimacy in young adult women. This research examines the relationship between fathering and intimacy. Therefore, the goal of this study is to provide an empirical overview of the extent of fathering's influence on intimacy in young adulthood in Medan City. In this section, the researcher will outline the conclusions in the form of a research summary, as well as methodological and practical suggestions for further research. Based on the analysis of the data obtained in this study, several things can be concluded as follows: This study shows the value of the coefficient of determination or R square on the quarter life crisis variable on subjective well-being of 0.042, which means that the influence of the independent variable (Fathering) on the dependent variable (Intimacy) is 4.2%. Based on the descriptive data of the study, it can be seen that the fathering scale has an empirical mean of 81.64, where this result is obtained through the calculation of the score given by respondents from the measuring instrument and the hypothetical mean of 70. Therefore, because the empirical mean result of fathering is above the hypothetical mean, overall the fathering of early adult women in Medan City is quite high. Based on the descriptive data of the study, it can be seen that the intimacy scale has an empirical mean of 107.04, where this result is obtained through the calculation of the score given by respondents from the measuring instrument and the hypothetical mean of 82.5. Therefore, because the empirical mean result of intimacy is above the hypothetical mean, overall the intimacy of early adult women in Medan City is quite high.